The Effects Of Purple Grape Juice (Vitis Vinifera) On Spermatozoa Motility Of Male Wistar Rats (Rattus Norvegicus) Exposed To Electric Cigarette Smoke - Ishak Raharjo Putranto; Dhega Anindita Wibowo; RR Mahayu Dewi Ariani; Donna Hermawati (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Infertility in men can be caused by decreased motility of spermatozoa. Electric cigarette smoke containing nicotine can produce free radicals that cause a decrease in sperm motility. Purple grape juice which contains flavonoids can act as antioxidants that can increase the motility of spermatozoa. Objective: To prove the effect of administering purple grape juice on sperm motility of male Wistar rats exposed to electric cigarette smoke.Methods: This research is an experimental study with a post-test-only control group design. Sample consisted of 28 male Wistar rats divided randomly into 4 groups, namely negative control, positive control (given electric cigarette smoke), treatment one (given electric cigarette smoke + purple grape juice 3 mL/day), and treatment two (given electric cigarette smoke + purple grape juice 5 mL/day). The adaptation was carried out for 1 week, followed by treatment for 4 weeks, then the sperm of Wistar rats were collected and the sperm motility of Wistar rats was examined. Statistical test used Saphiro Wilk and Kruskal Wallis test.Results: Progressive motility rate of K(-), K(+), P1, P2 groups consecutively: 58.33 ± 7,52; 26,66 ± 8,16; 31,66 ± 7,52; 43,33 ± 12,11. Non progressive motility rate of K(-), K(+), P1, P2 groups consecutively: 26,66 ± 10,32; 55 ± 8,36; 43,33 ± 12,11; 35 ± 12,24. Immotility rate of K(-), K(+), P1, P2 consecutively: 18,33 ± 9,83; 28,33 ± 14,71; 20 ± 6,32; 16,66 ± 5,16. Kruskal Wallis test found a significant difference in progressive motility (p=0.002) and non-progressive motility (p=0.005).Conclusion: Purple grape juice affects sperm motility of male wistar rats exposed to electric cigarette smoke.